Adjusting cell structure of polypropylene composite foams by controlling the size and dispersed state of NaCl particles during CO2 batch foaming process. (24th April 2020) - Liu, Ziqi; Qiu, Jian; Shi, Zhiyuan; Zhang, Shaofeng; Xing, Haiping; Li, Minggang; Shi, Yunfen; Tang, Tao
Abstract: In this work, a novel method for regulating cellular structure of polypropylene (PP) foam under CO2 batch foaming with water as disperse medium was established by addition of hydrophilic fillers (Such as NaCl). The presence of NaCl increased adsorption amount of water in PP/NaCl composites. As a result, both CO2 and adsorbed water acts as blowing agents during CO2 batch foaming. Thus the dispersed state and size of NaCl particles directly affect the mixed state of two blowing agents (water and CO2 ) and the competition between two types of heterogeneous nucleation from NaCl particles and PP crystals during foaming, which are the fundamental reasons for the formation of the foamed materials with different cellular structures, such as isolated large cell surrounded by uniform small cell structure, bimodal cell structure and homogeneous cell structure. Another unexpected finding was that the water absorption of PP/NaCl composites increased with the decrease of NaCl particle size, which is beneficial to play the in-situ cooling effect and co-blowing agent of absorbed water to control the foaming behavior of PP, and avoid the damage of foam mechanical properties due to the high content of filler. Graphical abstract: Image 1 Highlights: The presence of NaCl increased adsorption amount of water in PP/NaCl composites. The mixing state of water and CO2 in PP/NaCl composites was controlled by the NaCl dispersed state in PP matrix. The cellular structure of PP/NaCl foams depended on the mixing state of water and CO2 in PP/NaCl composites.